2020
DOI: 10.1192/j.eurpsy.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in cognitive functioning of patients at-risk for psychosis and healthy controls: Results from the European Gene–Environment Interactions study

Abstract: Background. Sex differences in cognitive functioning have long been recognized in schizophrenia patients and healthy controls (HC). However, few studies have focused on patients with an at-risk mental state (ARMS) for psychosis. Thus, the aim of the present study was to investigate sex differences in neurocognitive performance in ARMS patients compared with HC. Methods. The data analyzed in this study were collected within the multicenter European Gene–Environment Interactions study (11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
1
5
1
Order By: Relevance
“…Our results showed that men displayed significantly poorer social functioning than women upon presentation, while the levels of role functioning did not differ between sexes. In fact, the observed sex difference in social functioning is in keeping with many (Barajas et al, 2015;Rietschel et al, 2017;Walder et al, 2013), although not all (Cocchi et al, 2014;Menghini-Müller et al, 2020) previous studies which demonstrated that females with ARMS displayed better global psychosocial functioning relative to male counterparts. This is also in line with earlier research indicating that men had worse premorbid social adjustment than women in ARMS sample (Tarbox et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Our results showed that men displayed significantly poorer social functioning than women upon presentation, while the levels of role functioning did not differ between sexes. In fact, the observed sex difference in social functioning is in keeping with many (Barajas et al, 2015;Rietschel et al, 2017;Walder et al, 2013), although not all (Cocchi et al, 2014;Menghini-Müller et al, 2020) previous studies which demonstrated that females with ARMS displayed better global psychosocial functioning relative to male counterparts. This is also in line with earlier research indicating that men had worse premorbid social adjustment than women in ARMS sample (Tarbox et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…However, very few studies have examined sex difference in cognitive functions in at-risk populations (Ittig et al, 2015;Menghini-Müller et al, 2020;Riecher-Rössler et al, 2018). These limited data generally indicate lack of difference between sexes in cognitive performance or much less pronounced differences as compared to those observed in chronic schizophrenia (Ittig et al, 2015;Mendrek & Mancini-Marïe, 2016;Menghini-Müller et al, 2020). We also failed to find significant sex differences in cognitive functions in ARMS.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…There is reason to believe that the loss of oestrogen takes this female advantage away [ 3 ]. Prior to menopause, cognitive defects are much more marked in men with schizophrenia when compared to women [ 4 ]. This female advantage also appears to wane with oestrogen decrease [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%